Mapping the research structure on Crohn’s disease in PubMed and Web of Science (2014-2023) - Shirshahi, Saeid; Vesal Azad, Roya; Riahinia, Nosrat (AWARI, 2024)
This research aims to generate a thematic analysis and scientific mapping of Crohn's disease research in PubMed and Web of Science databases. The current research is descriptive-cross-sectional and uses a scientometric approach. The required data was collected from Web of Science and PubMed databases on December 23, 2022, and the collection method used was census type. The collected data includes all the documents from 2014 to 2023 in PubMed and Web of Science. Vosviewer 1.6 software was used to draw scientific maps. Gastrointestinal hepatology was the most relevant topic. The United States of America ranked first with 13% of all scientific productions, while Iran ranked 41st in the world. Scientific maps showed the importance of studies related to women. The findings showed the importance of age, nutrition, biomarkers, endoscopy, and their relationship with Crohn's disease. The position of Iran's studies in the field of Crohn's disease was not very favorable among the countries of the world, and scientific maps showed the importance of studies related to women and adults as well as young people and revealed the increase of this disease among women in recent years. The importance of the role of nutrition in the immune system and digestive system in Crohn's disease was also shown.